2023
DOI: 10.1002/adhm.202202670
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ligand Independent Tropism of siRNA‐LNP by Small Molecules for Directed Therapy of Liver or Myeloid Immune Cells

Abstract: Hepatic clearance of lipid nanoparticles (LNP) with encapsulated nucleic acids restricts their therapeutic applicability. Therefore, tools for regulating hepatic clearance are of high interest for nucleic acid delivery. To this end, this work employs wild‐type (WT) and low‐density lipoprotein receptor (Ldlr)−/− mice pretreated with either a leukotriene B4 receptor inhibitor (BLT1i) or a high‐density lipoprotein receptor inhibitor (HDLRi) prior to the injection of siRNA‐LNP. This work is able to demonstrate sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The first method employed DLS settings that we have used in earlier studies. Routinely we use DLS as it is done in the first method where we characterize for instance lipid nanoparticles for siRNA, at a DLS angle of 173.5° [15]. This method revealed that at a concentration of 1:10 diluted in phosphate‐buffered saline (PBS), the ink particles sized 1080 nm, but when they were diluted 1:100 in PBS, the size increased to 5615 nm (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first method employed DLS settings that we have used in earlier studies. Routinely we use DLS as it is done in the first method where we characterize for instance lipid nanoparticles for siRNA, at a DLS angle of 173.5° [15]. This method revealed that at a concentration of 1:10 diluted in phosphate‐buffered saline (PBS), the ink particles sized 1080 nm, but when they were diluted 1:100 in PBS, the size increased to 5615 nm (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that huge amounts of the ink are stored in vesicles of monocytes and macrophages and that this is owed to the large aggregations of the ink. Clinically usable nanoparticles such as lipid nanoparticles for siRNA [15], or liposomal carriers [20], do not affect the granularity of immune cells, which is likely based on the fact that these nano‐sized particles do not lead to large intracellular inclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The labeled nucleosomes were enriched by Dynabeads TM Streptavidin T1 following the manufacturer's instruction. Protein levels were determined with discovery-based proteomics (using label-free quantification) for relative protein concentrations (28). Briefly, in-gel digestion was performed on 40 µL of the proteins that were eluted from the beads in 1X LDS loading buffer (Thermo scientific) using trypsin (150 ng sequencing grade modified trypsin V5111; Promega) after reduction with 10 mmol/L dithiothreitol and alkylation with 55 mmol/L iodoacetamide proteins (29).…”
Section: Mass-spectrometry Analysis Of Aha Labeling Of Proteins After...mentioning
confidence: 99%
“…Active targeting can be executed with LNPs containing a target-specific ligand in the formulation, whereas passive targeting can be executed without targeting moiety [ 25 ]. Targeting moieties for active targeting mechanisms include antibodies [ 26 ], aptamers [ 27 ], small molecules [ 28 ] and proteins or peptides [ 29 ]. Passive targeting (EPR-effect) is influenced by factors such as the size and charge of the LNP, which depend on the molar composition of the different types of lipids used in the formulation [ 30 ].…”
Section: Vaccine Typesmentioning
confidence: 99%